Neuroendocrine, goblet cell and mixed adeno-neuroendocrine tumours of the appendix: updates, clinical applications and the future. (4th March 2017) - Clift, Ashley K.; Frilling, Andrea
ABSTRACT: Introduction : Appendiceal neuroendocrine neoplasms are rare, clinically challenging tumours that are typically incidentally diagnosed, have a poorly understood biology and have controversy surrounding their management. Most are adequately treated with appendectomy, and although distant metastases are rare, the threat of disease dissemination remains and current guidelines possess poor accuracy in terms of selecting patients requiring more extensive surgery, i.e. oncological right-hemicolectomy. Areas covered : In this article, we discuss the presentation and diagnostic work-up of patients with appendiceal neuroendocrine neoplasms, and also examine the evidence base for existing management strategies. We highlight controversies within the management of these tumours, and anticipate avenues for further progress. Although no longer classified as neuroendocrine neoplasms, we also discuss two related forms of tumours with neuroendocrine features – goblet cell cancers and mixed adeno-neuroendocrine carcinomas. Expert commentary : Existing guidelines for the treatment of appendiceal neuroendocrine neoplasms are derived from a limited evidence base and are unable to accurately predict which patients require extensive attempts at surgical disease control. Future advances in the field of improved patient selection for more extensive surgery may be possible with multi-factorial tumour assessment integrating morphological and molecular analyses.